2019
DOI: 10.15376/biores.14.2.2995-3011
|View full text |Cite
|
Sign up to set email alerts
|

Prices of raw-wood assortments in selected markets of central Europe and their development in the future

Abstract: The aim of the paper is to evaluate the price development of timber assortments in selected countries in Central Europe, to compare the prices and identify the factors influencing the prices, and to quantify the extent of their impact on the prices. A further aim is to predict the price development based on comparing various models for predicting time series of prices. The analyses of the price development was carried out for the assortments of spruce, fir, and beech sawlogs in Slovakia, Czech Republic, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…While time series models are widely used for forecasting in the forest sector ICCR'2 Some researchers found that the six-month ARIMA forecasts were the most accurate in predicting beech sawlog prices in Central Europe compared to linear and multivariate exponential smoothing models. As a result, they recommended that this model be used to guide management and trade decisions [13].…”
Section: Results and Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…While time series models are widely used for forecasting in the forest sector ICCR'2 Some researchers found that the six-month ARIMA forecasts were the most accurate in predicting beech sawlog prices in Central Europe compared to linear and multivariate exponential smoothing models. As a result, they recommended that this model be used to guide management and trade decisions [13].…”
Section: Results and Comparisonmentioning
confidence: 99%
“…This estimation is typically done using Maximum Likelihood Estimation (MLE). Once the parameters are estimated, the model can be used for forecasting [13]. Θ_Q, ..., Θ_{Q*seasonal} are the parameters of the seasonal moving average part.…”
Section: Sarimax Modelmentioning
confidence: 99%
“…The importance of the possibilities of deploying these innovative technologies in forestry operations is based on forecasts of the future development of raw-wood assortments prices [29] and requirements to ensure the sustainability of the industry [30].…”
Section: Introductionmentioning
confidence: 99%